DIAGNOSIS AND SURGICAL TREATMENT OF MELANOMA: A MINI REVIEW - Stevanovic, Goran; Momčilović, Stefan (Acta medicae Medianae, 2022)
Melanoma is a rare but the deadliest form of skin cancer. In the early stages, melanoma can be treated successfully by surgery and survival rates are high. However, in patients with metastases, survival rates drop significantly. Therefore, early and accurate diagnosis, prompt referral and proper management are crucial for ensuring the best prognosis. Also, multidisciplinary approach is necessary.The diagnosis of melanoma is usually made by dermoscopic examination of suspected pigmented lesions. Misdiagnosis of melanoma is one of the most common reasons for initiating lawsuits for wrong treatment, when it comes to pathologists and dermatologists, immediately after breast cancer.  Regarding the treatment of metastatic melanoma, in the last 10 years several new drugs have been developed that have significantly improved the prognosis of patients suffering from this disease. However, a majority of patients do not show a lasting response to these treatments. Thus, new biomarkers and drug targets are needed to improve the accuracy of melanoma diagnosis and treatment. This article discusses the current state of melanoma diagnosis and treatment based on the generally accepted consensus in this area and current national guidelines for treatment recommendations. The parts that remained open in the treatment algorithm (i.e. insufficiently clearly defined) are also mentioned.
Keywords: melanoma, diagnosis, treatment, surgery, dermoscopy